Risk of Periprosthetic Joint Infection after Posttraumatic Hip Arthroplasty following Acetabular Fractures - Schmidutz, Florian; Schreiner, Anna Janine; Ahrend, Marc-Daniel; Stöckle, Ulrich; Maier, Sven; Histing, Tina; Hemmann, Philipp (The Journal of Hip Surgery, 2024)
Background Raised complication rates have been reported for total hip arthroplasty (THA) in posttraumatic hip joints after acetabular fractures with prior open reduction and internal fixation (ORIF). The present study evaluated (I) postoperative surgical site infection and the risk of early infection following THA in posttraumatic hip joints after acetabular fractures and (II) the discriminatory ability of preoperative C-reactive protein (CRP) blood levels for periprosthetic joint infection (PJI).Materials and Methods Patients were included who had undergone THA (2014–2019) after prior ORIF, and nonsurgically treated acetabular fractures. Patients’ demographics and the duration between fracture and THA implantation were assessed. Preoperative diagnostic testing (laboratory results, hip aspirations) as well as the results of intraoperative microbiological swabs and sonication were also evaluated. Postoperative complications were recorded.Results Sixty-seven patients (51 men/16 women) were included, with a mean age of 54.7 ± 14.0 years (range: 18.0–82.9). The mean time between acetabular fracture and THA was 13.5 ± 14.9 years (0.2–53.5). Four subgroups were classified: subgroup I (nonsurgical, n = 15), subgroup II (complete removal of osteosynthesis, n = 8), subgroup III (partial removal of osteosynthesis, n = 15), and subgroup IV (remaining osteosynthesis, n = 29). Preoperative CRP blood levels were normal. CRP levels had no discriminatory ability to predict PJI (AUC: 0.43). Positive microbiological swabs were assessed in subgroups III (n = 1) and IV (n = 2). Complications during follow-up occurred in subgroups I (one aseptic loosening [6.7%]), III (one wound revision [6.7%], two low-grade infections [13.3%]), and IV (three low-grade infections [10.3%]).Conclusion High infection rates were found in patients with THA after acetabular fracture with remaining implants or partial implant removal. Serum CRP alone seems to be a poor predictor. Therefore, an extensive diagnostic algorithm can help to detect an occult infection, including preoperative hip aspiration (microbiological samples and measurements of synovial CRP, WBC, and alpha-defensin levels). Intraoperative tissue samples and sonication results should be obtained during THA implantation.
Keywords: acetabular fracture; total hip arthroplasty; PJI; posttraumatic hip osteoarthritis; THA